Biomechanical Comparison of Glycomer 631 and Glycomer 631 Knotless for Use in Canine Incisional Gastropexy. Issue 2 (23rd October 2012) - Arbaugh, Melissa; Case, J. Brad; Monnet, Eric
<x xml:space="preserve">Abstract</x> Objective To compare the load to failure of incisional gastropexy performed with standard glycomer 631 (G) and with knotless glycomer 631 (GV) in ex vivo model of gastropexy. Study Design Cadaveric study. Sample Population Cadaveric canine stomach and body wall (n = 24). Methods Specimens were divided into 4 groups based on suture type (G, GV) and size (3 metric, 2 metric). An incisional gastropexy was performed on all samples, and load to failure evaluated. Results Gastropexy with GV had significantly higher load to failure than gastropexy performed with G (P = .0006). Suture size had no significant effect on maximum load to failure (P = .36). The interaction between size of the suture and suture materials had a significant effect on the load to failure of the gastropexy (P = .0474). Knotless glycomer 631, 3 metric had significantly greater load to failure than G 3 metric (P = .0016) and G 2 metric (P = .0107). Conclusion A knotless suture appears to have comparable, if not greater load to failure than a standard suture of similar composition when used in canine incisional gastropexy in an acute ex vivo model.